Spanish National Remote Sensing Program, a way to achieve massive use of remote sensing data - Peces J.J.; Villa G.; Arozarena A.; Plaza N.; Tejeiro J.A.; Domenech E. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
Spanish National Remote Sensing Program (PNT) provides regular coverage of the Spanish territory with current and historical satellite imagery. This imagery is acquired with multi-user licenses for all Spanish Public Institutions, and processed once with geometric and radiometric processing agreed by experts of Spanish scientific community, and it is distributed to all users from Spanish Public Institutions. This way, we promote the massive use of remote sensing data. Spanish imagery is structured in three levels of spatial and temporal resolution: (i) High resolution: Images from 2 to 10 m of spatial resolution in panchromatic mode and from 10 to 30 m in multispectral mode. It is acquired a complete coverage every year with summer images. From 2005 to nowadays SPOT5 satellite is selected to provide that type of resolution. In future, with Spanish high resolution satellite called Ingenio, we will have several annual coverages. (ii) Medium resolution: Images from 10 to 15 m of spatial resolution in panchromatic mode and from 20 to 50 m in multispectral mode. It was planned to acquire at least four coverages every year, but since January 2008 all Landsat5 (TM) imagery captured over Spain is acquired. During 201, as well, Spot4 and Deimos1 images are being acquired. (iii) Low resolution: Multispectral images from 50 to 1000 m of spatial resolution, with a periodicity of 1 or 2 days. MODIS and MERIS sensors are the main source of this type of resolution. Nowadays, in PNT, more than 2000 images are processed every year to obtain derivate products such us georeferenced images, mosaics of images, etc. To reduce the time between the collection of data and the moment the information is available, PNT has designed a storage infrastructure suitable to the volume of information, an appropriate workflow, distribution control and an efficient spreading.